Scientology: die Grundlagen des Denkens - Hubbard, L. Ron (New Era Publ., 2007)
Suchen Sie grundlegende Antworten auf das Leben? Ist es möglich das umfangreiche Gebiet des Verstandes, des Geistes und des Lebens anzugehen und zu Grundprinzipien zu gelangen, die nicht nur die größten Rätsel erklären, sondern auch einen exakten, meßbaren Weg weisen, um die Rätsel zu lösen. Die Antwort ist ja! Sie werden die Grundprinzipien in diesem Buch finden. Sie sind einfach und doch sehr wirksam, und Sie werden dadurch, das Sie diese lesen und anwenden, Ihr Leben sowie das der umgebenden Menschen verändern. - After having fully unified and codified the subjects of Dianetics and Scientology came the refinement of their fundamentals. Originally published as a résumé of Scientology for use in translations into non-English tongues, this book is of inestimable value to both the beginner and advanced student of the mind, spirit and life. Equipped with this book alone, one can begin a practice and perform seeming miracle changes in the states of well-being, ability and intelligence of people. Contained within are the Conditions of Existence, Eight Dynamics, ARC Triangle, Parts of Man, the full analysis of Life as a Game, and more, including exact processes for individual application of these principles in processing. Here, then, in one book, is the starting point for bringing Scientology to people everywhere.